2018
DOI: 10.1002/mbo3.721
|View full text |Cite
|
Sign up to set email alerts
|

Myo‐inositol‐1‐phosphate synthase (Ino‐1) functions as a protection mechanism in Corynebacterium glutamicum under oxidative stress

Abstract: Reactive oxygen species ( ROS ) generated in aerobic metabolism and oxidative stress lead to macromolecules damage, such as to proteins, lipids, and DNA , which can be eliminated by the redox buffer mycothiol (AcCys‐GlcN‐Ins, MSH ). Myo ‐inositol‐phosphate synthase (Ino‐1) catalyzes the first committed step in the synthesis of MSH , thus playing a critical role in the growth of the organism. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Ins-1P is primarily formed by Myo-inositol-phosphate synthase (MIPS) catalyzing glucose-6-phosphate (Glc-6P) 60 , which is an important precursor substance of phosphatidyl- myo -inositol and mycothiol 61 . Ins-1P is an essential metabolite for growth and virulence in some bacteria 62 , 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Ins-1P is primarily formed by Myo-inositol-phosphate synthase (MIPS) catalyzing glucose-6-phosphate (Glc-6P) 60 , which is an important precursor substance of phosphatidyl- myo -inositol and mycothiol 61 . Ins-1P is an essential metabolite for growth and virulence in some bacteria 62 , 63 .…”
Section: Discussionmentioning
confidence: 99%
“…About proteins involved in the transport and metabolism of carbohydrate, proteins corresponding to the utilization of alternative carbon sources are induced, including Myo-inositol catabolism IolB protein (emb|CDP49182.1|), as it happens during unfavorable conditions in Corynebacterium glutamicum (Chen et al, 2019). The pentose phosphate pathway, including the phosphoketolase pyrophosphate (emb|CDP48739.1|) and the ribose-5-phosphate isomerase 3 (emb|CDP49834.1|), is also enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning lipid and transport metabolism, the induction of inositol-1-phosphate synthase (emb|CDP49767.1|) and of acyltransferase PslC (emb|CDP49388.1|) indicates enhanced biosynthesis of phospholipids, in accordance with the observed effect of salt on membrane fatty acids. These proteins are also involved in stress response in Serratia plymuthica and C. glutamicum (Nurlinawati et al, 2015; Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…d-myo-inositol supplement both orally (400 mg/kg) and intraperitoneally (200 and 800 mg/kg) suppressed inflammation in rats with adjuvant disease [119]. Moreover, myo-inositol-1-phosphate synthase (Ino-1) deletion in bacteria (Actinobacteria Corynebacterium glutamicum) increased production of ROS and decreased cell viability suggested that Ino-1 might have an effect on oxidative stress resistance [120]. Because of its ability to downregulate inflammation and cytokine release, it has been recently speculated that myoIns might be beneficial for Sars-CoV-2 patients [121].…”
Section: Other Health-beneficial Effectsmentioning
confidence: 99%